إختبار كفاءة سوق إندونيسيا للأوراق المالية عند المستوى الضعيف - حواسي, عائدة; بوالكور, نور الدين (جامعة الوادي - University of Eloued, 2023)
This study aims to test the efficiency of the Indonesian stock market at the weak level, on the basis of the daily data of the closing prices of the IDX index of the Indonesian stock market, during the period between 01/01/2017 and 31/12/2021, by testing the random walk hypothesis of the time series using unitary root tests: Dickey Fuller Expanded ADF, Phillips-Peron PP test, autocorrelation test and normal distribution test. The study concluded that the IDX composite index series is characterized by instability and does not follow a normal distribution, as it is characterized by random movement during the study period, meaning that the Indonesian stock market is an efficient market at the weak level, which means that it responds quickly and to a high degree to the information received by the market.
Indonesia Securities Market Efficiency Test at Weak Level
مقال
Keywords: نموذج السير العشوائي ; إستقرارية السلاسل الزمنية ; الأسواق المالية ; الكفاءة عند المستوى الضعيف: Random walk model; Time series stability; Financial markets; Efficiency at the weak level .